Revision of the subgenus Orientostichus Sciaky & Allegro in Southeast China, with descriptions of seven new species of the Pterostichus prattii Bates species group (Coleoptera: Carabidae: Pterostichini) - Yin, Wen-Qi; Chen, Jia-Heng; Shi, Hong-Liang (Zootaxa, 2024)
The subgenus Orientostichus Sciaky & Allegro, 2013 from Southeast China is reviewed. A total of eleven species were recognized from this area, all belonging to the Pterostichus prattii Bates, 1890 species group. They are mainly differentiated by the characters of pronotum basal foveae, elytral microsculpture, male sexual modification on sternite VII, and endophallus of male genitalia. Seven new species are described: Pterostichus (Orientostichus) sinuosus sp. nov. (type locality: Guangfuding, Guangxi), P. (O.) shan sp. nov. (Nanling, Guangdong), P. (O.) luoxiaoensis sp. nov. (Qiyunshan, Hunan), P. (O.) separatus sp. nov. (Tianmu Mt., Zhejiang), P. (O.) skanda sp. nov. (Tianmu Mt., Zhejiang), P. (O.) fujianensis sp. nov. (Luoboding, Fujian), P. (O.) deliquus sp. nov. (Ziyundong mt., Fujian). P. (O.) matalini Fedorenko, 2023 is newly recorded from China (Jian’ou, Fujian).